2010 2nd International Conference on Education Technology and Computer 2010
DOI: 10.1109/icetc.2010.5529662
|View full text |Cite
|
Sign up to set email alerts
|

eSelf-assessment: A case study in English language learning (Hong Kong) for enhancing writing and oral presentation skills

Abstract: The purpose of this paper is to share the experience of an application on an English learning programme for engineering students at the university, which features eSelf-assessment on an open-source e-learning platform. This paper demonstrates the implementation of eSelf-assessment to show the flow of students' tasks, the first and second repetitive processes for students in different level of learning ability. A survey was conducted to collect students' satisfaction and effectiveness of independent online lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It enables the students to think and analyse their own learning skills which assists them to enhance their work performance on the basis of the feedback they obtain [7]. They can take assessment regarding any lecture of any module.…”
Section: Bmentioning
confidence: 98%
“…It enables the students to think and analyse their own learning skills which assists them to enhance their work performance on the basis of the feedback they obtain [7]. They can take assessment regarding any lecture of any module.…”
Section: Bmentioning
confidence: 98%
“…In this respect, numerous studies (Wingate 2010;Hubner et al 2010;Li 2010 ;Wallace et al 2004;Worley 2008 ) have indicated that writing and reading skills are significant in the business sector, as students should have all the basic knowledge behind writing, reading, reflecting, and very high-level thinking, and this can be achieved by practice and interaction during class time or through the discussion board and forums via the blackboard and Moodle FLECS facility (Tucker et al 1998). These skillsresearch, writing, technology, information, critical thinking, reading, debate and presentationcan be developed by using assessments such as reflective journals and report writing.…”
Section: Communication Skillsmentioning
confidence: 99%
“…Integrating and mixing these skills in the unit will promote and enhance students' personalities and increase their confidence in approaching their studies and workplace in the future. Several studies (Yang et al 2008;Worley 2008 ;Pavolvich et al 2009;Li 2010 ;Kuzma 2011;Van Deursen et al 2011) indicate that integrating these skills in various assessments (i.e. reflective journal, business plan and prototype, discussion forum, presentation, and final examination) will make them more challenging, exciting, and interactive, and encourage students to complete them before or on time.…”
Section: Introductionmentioning
confidence: 99%